Plasmonic sensors with an ultra-high figure of merit. (24th December 2019) - Liu, Zhengqi; Liu, Guiqiang; Liu, Xiaoshan; Fu, Guolan
Abstract: We propose and numerically demonstrate a high-quality hybridized resonant platform, composed of a one-dimensional metal grating and a dielectric cavity. Under a moderate oblique illumination, an ultra-high spectral quality (Q) factor of 1375 is achieved, which shows orders of magnitude larger than that of the system under normal excitation. The high-Q mode results from the strong coupling effect between the surface plasmon polariton of the metal grating and the photonic mode of the dielectric cavity. Based on this hybridized plasmonic resonator, a high-performance sensing scheme with the spectral sensitivity ( S ) up to 800 nm/RIU (refractive index unit, RIU) is further introduced. Moreover, the figure of merit reaches 1337, indicating a new record for both the localized or propagating surface plasmons based sensors. These features could find applications in sensing and detecting devices, plasmonic switches, and light flow modulators.